LLC Resonant Converter Topologies For Plug-In Electric Vehicle Battery Charging - Shahzad, Muhammad Imran (2017)
Recent improvements in battery technology and reduction in price have intensified interests in electrical vehicles (EVs) as these provide best means for pollution free and efficient transportation necessary for the sustainable development of the whole world. In near future, plug-in electrical vehicles (PEVs), which are equipped with on-board chargers, are expected to dominate the automobile market. Most commonly used on-board chargers consist of two stages with AC/DC converter as first stage and DC/DC converter as second stage. This thesis focuses on second stage whose function is to regulate charging voltage and current in accordance with battery’s charging requirements. The terminal voltage of EV battery varies over wide range during usage and it may discharge up to normally depleted or deeply depleted states. Therefore, the main challenge for DC/DC converter designer is to realize wide range of output voltage and current while maintaining good efficiency so that the converter is able to revive deeply depleted battery. To this end, this thesis contributes five novel topologies of LLC resonant converter for the DC/DC stage of on-board PEV battery charger which are: double LLC tank resonant converter, double LLC tank resonant converter with hybrid-rectifier, hybrid-bridge LLC resonant converter, hybrid-bridge LLC resonant converter with hybrid-rectifier, and interleaved LLC resonant converter with series connected voltage doublers. The first topology uses frequency control to achieve only depleted battery charging voltage range. Whereas, the other four topologies use mode changing with switching frequency control to extend the output voltage range for reviving deeply depleted battery, compared with conventional counterparts which use complex control techniques. Moreover, all the proposed topologies operate below resonance frequency for most extensively used normal battery charging range, therefore, power switches operate with ZVS and rectifier diodes with ZCS. The proposed topologies are designed for charging lithiumion PEV battery pack with terminal voltage as 420V when fully charged, 250V when depleted, and 100V or less when deeply depleted. The circuit configuration, analysis of operation, gain characteristics and design procedure of all the topologies are presented in details. Finally, all the proposed topologies are implemented and tested in laboratory and also simulated using MATLAB Simulink environment with 400V DC input and 1.5 kW maximum output power. The captured experimental and simulation results are presented in this thesis for validation of operation and performance of proposed converter topologies. The presented results showed that the four proposed topologies can effectively charge both normally depleted as well as deeply depleted battery, while the first topology can achieve only normally depleted battery voltage range. On the other hand, last two topologies have shown widest output voltage range of 50V–420V. Therefore, last two topologies have the ability to charge even very deeply depleted batteries. All the proposed topologies have peak efficiency higher than 95% at peak output power. However, the last topology which is interleaved LLC resonant converter with voltage doubler rectifier has highest efficiency of 95.65%. Moreover, this topology also has widest output voltage range of 50V–420V, so it can be considered as the best one among all the proposed topologies.